'I think sometimes that dads are kind of forgotten (…) so it's nice that we also get a voice.': work-life experiences of employed U.S. fathers caring for a child with special health care needs. Issue 5 (20th October 2022) - Sellmaier, Claudia; Buckingham, Sarah R.
ABSTRACT: Meeting work and family demands can be challenging for all families, and even more challenging when raising a child with special health care needs. This current qualitative study interviewing 16 working fathers who care for a child with special health care needs, examines U.S. fathers' experiences of work-family-community fit, adding to the still limited body of work-life research about fathers. Fathers were recruited through social media calls, blog posts, and email listservs of family support groups. Most participating fathers were employed full time, married/partnered, and cared on average for two children, ranging from 1 to 20 years in age. Thematic data analysis of in-depth telephone interviews demonstrated that fathers relied on work, family, and community resources to meet work and care demands. Fathers employed strategic decision-making selecting jobs that provided flexibility and access to resources such as health insurance. Formal and informal community supports were critical, but not always adequate or easy to access, resulting in the need for ongoing parental advocacy. Inadequate community and workplace resources were compensated by the family system. Work and care responsibilities did not only create stress but provided respite and positive experiences. Implications for future research, and practice and policy changes are being discussed.